Numerical Investigation of Hot Helium Flow Homogenizer on Inter-Unit Flow Rate Uniformity of HTGR Once Through Steam Generator - Qin, Haiqi; Luo, Xiaowei; Li, Xiaowei; Wu, Xinxin (Frontiers in Energy Research, 2022)
High working temperature is a major feature of the high temperature gas-cooled reactor (HTGR). The helical tube once through steam generator (OTSG) should maintain appropriate temperature uniformity. The temperature non-uniformity of the HTGR OTSG includes the in-unit and inter-unit temperature non-uniformity, while the latter is mainly induced by the inter-unit flow rate non-uniformity of primary-side hot helium, which is significantly affected by the inlet structure. In this work, a new inlet structure with a hot helium flow homogenizer is designed, and its flow distribution characteristics are numerically investigated. Accordingly, the optimal geometrical parameters are determined, such as the circular hole diameter on the end wall, the square hole size, and arrangement on the cylinder wall. Increasing the resistance of the flow homogenizer with non-uniformly arranged square holes (NUASHs) can improve inter-unit flow rate uniformity because it decreases the effect of static pressure difference caused by dynamic pressure. Two design parameters (resistance coefficient and flow area ratio of the square hole on both sides) are introduced to evaluate the structure effect of the hot helium flow homogenizer on inter-unit flow rate distribution. They are recommended within the ranges of (7.81–22.42) and (0.53–1.64), respectively. In these recommended ranges, the suction phenomenon near the hot helium inlet can be effectively suppressed, with the critical resistance coefficient of 7.63. By coupling with 19 heat exchange units, the overall performance of the hot helium flow homogenizer is better than that of the current inlet structure with a baffle, with the maximum inter-unit flow rate deviation decreased from 2.97% to 0.30%. This one-magnitude enhancement indicates that the hot helium flow homogenizer with NUASHs is a promising solution to improve inter-unit flow rate uniformity of the HTGR OTSG.